Pengaruh Strategi Pembelajaran Active Knowledge Sharing Terhadap Keaktifan Belajar Siswa Kelas X SMK Negeri 1 Angkola Timur - Dedi Azhari STM; Sri Utami Kholilla Mora Siregar; Kasmawati (Universitas Gara Nusantara Padangsidimpuan, 2024)
The background of the problem in class The aim of this research is to determine the effect of active knowledge sharing learning strategies on student learning activeness and student learning responses to rectilinear movement material at SMK NEGERI 1 ANGKOLA TIMUR. This research is descriptive research involving class (XB) and class (XA). Data was collected through observation sheets. Observation data were analyzed using the learning activity percentage formula. The results of the observation sheet analysis show that after being given the active knowledge sharing learning strategy, the resulting scores were, class (XA) got 85.31% with the